Gut morphology and gene expression in obesity: Short review and perspectives. (August 2018) - Ferreira, B.A.M.; Sala, P.; Fonseca, D.C.; Heymsfield, S.B.; Waitzberg, D.L.
Summary: Obesity, a multifactorial and polygenic condition, is considered one of the great global public health problems of our time. The intestinal microbiome should be considered as a set of genetic factors that, together with the host genotype and lifestyle (consumption and energy expenditure), contribute to the pathophysiology of obesity. Increasing evidence showed an increased proportion of bacterial phylum Firmicutes and reduced concentrations of Bacteroidetes in obese as compared to normal weight humans. Studies report that DNA methylation patterns in the blood are associated with intestinal microbiota profiles and suggest that the microbiota and its metabolites influence genomic reprogramming. Investigations of the intestinal microbiota and its impact on genomic changes and their relationship to the risk of developing obesity provide opportunities to establish the basis for incorporating biological individuality into recommendations with significant therapeutic potential.